Four new records for the vascular flora of Bangladesh (Bangladesh Journal of Plant Taxonomy, 2023)
This study records two species of Pteridophytes, viz., Hemionitis cordata Roxb. ex Hook. & Grev. and Ophioglossum nudicaule L.f. of Pteridaceae and Ophioglossaceae, and two species of Angiosperms, viz., Bacopa australis V.C. Souza and Salvia misella Kunth of Plantaginaceae and Lamiaceae, respectively, for the first time in Bangladesh, based on the plant specimens collected during our recent botanical explorations conducted in selected areas of Bagerhat, Barguna, and Cumilla districts. A detailed taxonomic description with key characters, notes on ecology, uses, distribution, distinctness from other similar taxa, representative specimens examined, and photographs of each of these four species have been provided.Bangladesh J. Plant Taxon. 30(1): 21-30, 2023 (June)